Contrast‐enhanced ultrasound for differential diagnosis of malignant and benign ovarian tumors: systematic review and meta‐analysis. (September 2015) - Ma, X.; Zhao, Y.; Zhang, B.; Ling, W.; Zhuo, H.; Jia, H.; Li, P.
Abstract Objective To assess the performance of contrast‐enhanced ultrasound (CE‐US) in the differential diagnosis of malignant and benign ovarian tumors. Methods We conducted a comprehensive literature search of PubMed and EMBASE to identify published articles evaluating the diagnostic potential of CE‐US for the differentiation of benign and malignant ovarian tumors. Inclusion criteria were: (1) the study assessed the accuracy (or sensitivity and specificity) of CE‐US for diagnosis of benign and malignant ovarian tumors; (2) it used surgery and histopathology as the reference standard for distinguishing between benign and malignant tumors; (3) it included data allowing construction of a 2×2 contingency table for true‐ and false‐positives and negatives. We present summary sensitivity, specificity, diagnostic odds ratio (OR) and areas under the summary receiver–operating characteristics curves (AUCs). Results Preliminary screening identified 103 papers, of which 11 fulfilled our predefined inclusion criteria and underwent final analysis. The pooled sensitivity and specificity of CE‐US for diagnosis of benign and malignant ovarian tumors were 93% (95% CI, 89–96%) and 95% (95% CI, 92–96%), respectively. The pooled diagnostic OR was 171.2 (95% CI, 65.9–444.6) and the AUC was 0.98. I2 values of sensitivity, specificity and diagnostic OR were 38.3%, 31.7% and 48.4%, respectively, all indicating moderate heterogeneity. Conclusions The evidence from available studies suggests CE‐US is useful for discriminating between benign and malignant ovarian tumors; however, further studies are needed to examine whether CE‐US has improved diagnostic test accuracy compared with that of standard two‐dimensional Doppler sonography. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.